MOTIVASI INDONESIA MELAKUKAN KERJASAMA DENGAN KOREA SELATAN DALAM PENGADAAN PANSER TARANTULA TAHUN 2009-2013 - Akas Respati; Tri Joko Waluyo (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The purpose of this research is to explain general descripion Indonesia choose South Korea in the procurement of armored vehicles, This research method used kualitative research. This research is focused to discuss about is to find out the reason why Indonesia choose South Korea in the procurement of tarantula Panzer. This research used the realism perspective. The research also used state-level analysis.Based on the data analysis, it is concluded that the motivation for Indonesia to cooperate with South Korea in the procurement of armored tarantulas in 2009-2013 is because South Korea is a defense cooperation partner. Indonesia has several reasons or interests. In accordance with Indonesia's interests to modernize domestic military equipment, and build the independence of its defense industry so that it does not depend on one country alone and wants to carry out military cooperation at a lower cost, this is because South Korea offers cooperation in accordance with Indonesia's interests, namely by having Transfer of Technology, a cheap funding system, the absence of negative sentiment from America and there is no threat of an embargo.  Keywords: Cooperation, Armored vehicles, National Interest, defense Equipment.